Synthesis, Antimicrobial Effect and Lipophilicity‐Activity Dependence of Three Series of Dichained N‐Alkylammonium Salts. Issue 41 (5th November 2019) - Benkova, Marketa; Soukup, Ondrej; Prchal, Lukas; Sleha, Radek; Eleršek, Tina; Novak, Martin; Sepčić, Kristina; Gunde‐Cimerman, Nina; Dolezal, Rafael; Bostik, Vanda; Bostik, Pavel; Marek, Jan
Abstract: Quaternary ammonium salts belong to the group of cationic surfactants and their structure, especially the length of the alkyl chain, plays a significant role in its activity against various microorganisms. Globally, there is a growing need to develop novel compounds due to the increasing resistance of microorganisms to antimicrobial agents. Three series of quaternary ammonium compounds based on dichained N ‐alkylammonium salts were synthesized with different carbon chain lengths (C8, C10, C12, C14, C16 ). These compounds were characterized with analytical methods and tested in vitro for antibacterial, antifungal, antiviral and antialgal activities. In addition, the determination of their critical micelle concentrations, lipophilicity and cytotoxicity were likewise performed to assess potential lipophilicity‐activity dependence. Almost all compounds showed a high efficacy against bacterial and fungal strains. Significant effects against Varicella zoster virus and algae were also noticed. Some of novel drugs outperformed standard benzalkonium salts. The expected trend of the correlation of an increase of cytotoxicity with the length of carbon chain was confirmed. These compounds show a higher potential as disinfectants rather than antiseptics due to their cytotoxic potential and low selectivity for microbes over mammalian cells. Abstract : In this experimental paper, we report on the synthesis, analysis, surface properties and biological evaluation of surfactants based on quaternary ammonium compounds as potential disinfectants. Three series of quaternary ammonium compounds based on dichained N‐alkylammonium salts were synthesized and characterized. Afterwards the compounds were tested in vitro for antibacterial, antifungal, antiviral and antialgal activities. In addition, the determination of their critical micelle concentrations, lipophilicity and cytotoxicity were likewise performed to assess potential lipophilicity‐activity dependence.